A decomposition based memetic algorithm for multi-objective vehicle routing problem with time windows. (October 2015) - Qi, Yutao; Hou, Zhanting; Li, He; Huang, Jianbin; Li, Xiaodong
Abstract: Multi-objective evolutionary algorithm based on decomposition (MOEA/D) provides an excellent algorithmic framework for solving multi-objective optimization problems. It decomposes a target problem into a set of scalar sub-problems and optimizes them simultaneously. Due to its simplicity and outstanding performance, MOEA/D has been widely studied and applied. However, for solving the multi-objective vehicle routing problem with time windows (MO-VRPTW), MOEA/D faces a difficulty that many sub-problems have duplicated best solutions. It is well-known that MO-VRPTW is a challenging problem and has very few Pareto optimal solutions. To address this problem, a novel selection operator is designed in this work to enhance the original MOEA/D for dealing with MO-VRPTW. Moreover, three local search methods are introduced into the enhanced algorithm. Experimental results indicate that the proposed algorithm can obtain highly competitive results on Solomon׳s benchmark problems. Especially for instances with long time windows, the proposed algorithm can obtain more diverse set of non-dominated solutions than the other algorithms. The effectiveness of the proposed selection operator is also demonstrated by further analysis. Abstract : Highlights: We develop a memetic algorithm following the framework of MOEA/D for MO-VRPTW A special selection operation is designed according to the character of MO-VRPTW. The proposed algorithm periodically employs three types of local search methods. The proposed algorithm performs well on Solomon׳s problems with long time window.